Coupled heat and moisture transport in damaged concrete under an atmospheric environment. (15th July 2017) - Min, Hongguang; Zhang, Weiping; Gu, Xianglin; Černý, Robert
Highlights: A model was proposed and solved for coupled heat and moisture transport in concrete. A method to determine thermogradient and hygrogradient coefficients was presented. Moisture transport, temperature and humidity distributions were obtained in damaged concrete. Coupled heat and moisture has a significant effect on moisture transport in concrete. Effects of heat transfer and concrete damage on moisture transport should be considered. Abstract: This paper presents thermogradient and hygrogradient coefficients as indicators for evaluation of coupled effects of heat and moisture transport in concrete. A numerical model for coupled heat and moisture transport was established and solved as well as a method to determine thermogradient and hygrogradient coefficients. Effects of temperature and humidity gradients were investigated through experiments, which covered also the effects of damage on moisture transport, temperature and humidity distributions along with coupled transport. The experimental results showed that temperature and humidity gradients accelerated moisture transport along with increased damage. In addition, the effect of temperature gradient on temperature distributions was significant, while the effect of humidity gradient was small. However, both temperature and humidity gradients had significant effects on relative humidity distributions. Hence, coupled heat and moisture transport in concrete had a significant effect on moisture transport, and the effect of damage on moisture transport must be considered when determining humidity field in damaged concrete.